Negative past experience, image incongruence, corporate wrongdoing and brand forgiveness among islamic banking customers - Abd Rashid, Muhammad Hafiz; Muhamat, Amirul Afif; Hamzah, Muhammad Iskandar; Mansor, Aida Azlina (2025)
Research on the relationship between brand transgression and brand forgiveness is notably limited, especially in the context of Southeast Asian customers. Therefore, this study aims to contribute insights to existing literature by examining how brand transgression, represented by negative past experience, image incongruence, and corporate wrongdoing, influences brand forgiveness among Islamic banking customers in Malaysia. The increasing interest in negative brand relationships has prompted questions about their impact on brand forgiveness. Thus, this theoretical argument, lacking empirical evidence, requires statistical validation. This study utilized a non-probability purposive sampling technique to survey customers who had negative experiences with Islamic banking services in the Klang Valley area. Analysis of 211 usable responses included descriptive statistics, exploratory factor analysis, and multiple regression. The findings indicate that image incongruence and corporate wrongdoing significantly affect brand forgiveness, while negative past experiences do not. The paper also discusses research implications and suggestions for future studies.